Joint performance of laser-TIG double-side welded 5A06 aluminum alloy - 陈彦宾 苗玉刚 李俐群 吴林 (Transactions of Nonferrous Metals Society of China, 2009)
The influence of welding parameters on mechanical properties and microstructure of the welds of laser-TIG double-side welded 5A06 aluminum alloy was investigated. The results show that the weld cross-sectional shape has an intimate relation with the mechanical properties and microstructure of the welds. The symmetrical ＂X＂ cross-section possesses a relatively higher tensile strength and elongation than the others, about 91% and 58% of those of base metal, respectively. The good weld profiles and free defects are responsible for the improvement of tensile properties. Due to low hardness of the fusion zone, this region is the weakest area in the tensile test and much easier to fracture. The loss of Mg element is responsible for the decrease of mechanical properties of the joints. The microstructure of ＂X＂ cross-section has an obvious difference along the direction of weld depth, and that of the ＂H＂ cross-section is consistent and coarse.